Generalized fractional kinetic equations involving incomplete Aleph - function - Arya, Jagdish Chandra (International Journal of Mathematical Research, 2023)
Due to the great importance of the fractional kinetic equations, many authors discussed the generalizations of fractional kinetic equation involving various special functions. The purpose of this paper is to obtain the new generalization of fractional kinetic equation pertaining to the incomplete Aleph-function. The solution of the fractional kinetic equations obtained here by using Laplace and Sumudu transforms method. The Riemann-Liouville fractional integral operator is used to obtain the required results. The Solution of the generalized fractional kinetic equation are obtained by using the definition of incomplete Aleph function. The result discussed here can be used for the study of the chemical composition change in stars like the Sun. The solution rendered here are in compact forms suitable for numerical computation. Some special cases involving incomplete I –functions and incomplete H –functions are also considered.